MODEL LATIHAN WICKET KEEPING CRICKET BERBASIS OPEN SKILL PADA ATLET POPB CRICKET DKI JAKARTA - Dede Abdurohman; Andi Hasriadi Hasyim; Mastri Juniarto (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study explains how to develop an open skill-based cricket wicket keeping exercise model for DKI Jakarta POPB cricket athletes, using Research and Development research methods, in the small group test there were 17 athletes from the Sustainable Achievement Sports Development (POPB). The validation test used is an expert justification test with 3 (three) experts in the field of cricket. In the expert justification test, the design of the cricket-keeping wicket exercise model was made and developed, then tested until it was finally consulted and assessed by experts in the field of cricket. The researcher initially made a product design of 17 training models, then the final result of the justification test by experts, became 16 kinds of variations of the cricket keeping wicket exercise model. The results of this study are intended to serve as a reference for cricket coaches in the future. In order to be able to make a valuable contribution to the development of cricket coaching knowledge in Indonesia, especially in DKI Jakarta, especially in the application of the cricket-keeping wicket training model to improve the basic technical skills of cricket keeping specialists.